Nb2O5/graphene nanocomposites for electrochemical energy storage1. Issue 74 (13th August 2015) - Arunkumar, Paulraj; Ashish, Ajithan G.; Babu, Binson; Sarang, Som; Suresh, Abhin; Sharma, Chithra H.; Thalakulam, Madhu; Shaijumon, Manikoth M.
<x xml:space="preserve">Abstract</x> Here we report the synthesis of Nb2O5/graphene nanocomposites, through a simple hydrothermal method, with Nb2O5 nanoparticles anchored on reduced graphene oxide sheets.